Pengembangan Perangkat Pembelajaran Berorientasi Model Pembelajaran Inkuiri pada Materi Struktur dan Fungsi Jaringan Tumbuhan untuk Melatih Kemampuan Berpikir Kreatif Peserta Didik - Masra Latjompoh; Jusna Ahmad; Winda Minarti Jusuf (Jurnal Penelitian Pendidikan IPA, 2023)
This research is a development research that aims to produce learning tools in the form of Learning Implementation Plans (RPP), Student Worksheets (LKPD) and Creative Thinking Tests oriented to inquiry learning models that are, practical and effective, so that they can be used in the learning process. The results showed that the quality of the products produced based on practicality aspects in limited trials met very practical criteria with an average value of 95. In the broad trial it met very practical criteria with an average score of 100 and the response assessment of learners got a score of 50 on the limited trial and a score of 101 on the broad trial. The results of the creative thinking test field test are limited to the average value of the pretest answers, namely the Elaboration indicator at 5.3%, then the Fluency indicator at 3.3%, then Flexibility at 3.1% and the lowest is Originality at 0.2%. The average results of the post-test answers to students' creative thinking ability in the limited test found that the most percentage was the Fluency indicator at 15.9%, then the Elaboration indicator at 12.6%, then Flexibility at 6.3% and the lowest was Originality at 1%. In the main field test, the average value of the pretest answer is the Fluency indicator of 2.9%, then the Elaboration indicator of 2.6%, then Flexibility of 2.4% and the lowest is Originality, which is 0.1%. The average result of the post-test answers to the creative thinking ability of students in the main field test was found that the most percentage was the Fluency indicator of 5.2%, then the Elaboration indicator of 4.8%, then Flexibility of 3.9% and the lowest was Originality, which was 1%.